Policy Choices for Progressive Realization of Universal Health Coverage; Comment on “Ethical Perspective: Five Unacceptable Trade-offs on the Path to Universal Health Coverage” - Viroj Tangcharoensathien; Walaiporn Patcharanarumol; Warisa Panichkriangkrai; Angkana Sommanustweechai (International Journal of Health Policy and Management, 2017)
In responses to Norheim’s editorial, this commentary offers reflections from Thailand, how the five unacceptable trade-offs were applied to the universal health coverage (UHC) reforms between 1975 and 2002 when the whole 64 million people were covered by one of the three public health insurance systems. This commentary aims to generate global discussions on how best UHC can be gradually achieved. Not only the proposed five discrete tradeoffs within each dimension, there are also trade-offs between the three dimensions of UHC such as population coverage, service coverage and cost coverage. Findings from Thai UHC show that equity is applied for the population coverage extension, when the low income households and the informal sector were the priority population groups for coverage extension by different prepayment schemes in 1975 and 1984, respectively. With an exception of public sector employees who were historically covered as part of fringe benefits were covered well before the poor. The private sector employees were covered last in 1990. Historically, Thailand applied a comprehensive benefit package where a few items are excluded using the negative list; until there was improved capacities on technology assessment that cost-effectiveness are used for the inclusion of new interventions into the benefit package. Not only costeffectiveness, but long term budget impact, equity and ethical considerations are taken into account. Cost coverage is mostly determined by the fiscal capacities. Close ended budget with mix of provider payment methods are used as a tool for trade-off service coverage and financial risk protection. Introducing copayment in the context of feefor-service can be harmful to beneficiaries due to supplier induced demands, inefficiency and unpredictable out of pocket payment by households. UHC achieves favorable outcomes as it was implemented when there was a full geographical coverage of primary healthcare coverage in all districts and sub-districts after three decade of health infrastructure investment and health workforce development since 1980s. The legacy of targeting population group by different prepayment mechanisms, leading to fragmentation, discrepancies and inequity across schemes, can be rectified by harmonization at the early phase when these schemes were introduced. Robust public accountability and participation mechanisms are recommended when deciding the UHC strategy.